Immunomodulatory Effects of Lactobacillus plantarum Lp62 on Intestinal Epithelial and Mononuclear Cells. (30th June 2016) - Ferreira dos Santos, Thalis; Alves Melo, Tauá; Almeida, Milena Evangelista; Passos Rezende, Rachel; Romano, Carla Cristina
Abstract : Probiotic lactic acid bacteria are known for their ability to modulate the immune system. They have been shown to inhibit inflammation in experiments with animal models, cell culture, and clinical trials. The objective of this study was to elucidate the anti-inflammatory potential of Lactobacillus plantarum Lp62, isolated from cocoa fermentation, in a cell culture model. Lp62 inhibited IL-8 production by Salmonella Typhi-stimulated HT-29 cells and prevented the adhesion of pathogens to these epithelial cells. The probiotic strain was able to modulate TNF- α, IL1- β, and IL-17 secretion by J774 macrophages. J774 activation was reduced by coincubation with Lp62. PBMC culture showed significantly higher levels of CD4 + CD25 + T lymphocytes following treatment with Lp62. Probiotics also induced increased IL-10 secretion by mononuclear cells. L. plantarum Lp62 was able to inhibit inflammatory stimulation in epithelial cells and macrophages and activated a tolerogenic profile in mononuclear cells of healthy donors. These results indicate this strain for a possible application in the treatment or prevention of inflammatory diseases.